2023
DOI: 10.3892/br.2023.1671
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori extract induces purified neutrophils to produce reactive oxygen species only in the presence of plasma

Tran Thai,
Chalida Chuenchom,
Wachiraporn Donsa
et al.

Abstract: H. pylori is a bacterial pathogen infecting over half of the world's population and induces several gastric and extra-gastric diseases through its various virulence factors, especially cagA. These factors may be released from the bacteria during interactions with host immune cells. Neutrophils play key roles in innate immunity, and their activity is regulated by plasma factors, which can alter how these cells may interact with pathogens. The aim of the present study was to determine whether purified neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…IL-8 secreted from CD4 + T cells recruited CXCR1/2-expressed neutrophils to the inflammation site [33]. The Neutrophils promote inflammation by generating reactive oxygen species (ROS) [19,34]. In this study, we established Cx1Mab-1 which recognizes mCXCR1 with high sensitivity (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 secreted from CD4 + T cells recruited CXCR1/2-expressed neutrophils to the inflammation site [33]. The Neutrophils promote inflammation by generating reactive oxygen species (ROS) [19,34]. In this study, we established Cx1Mab-1 which recognizes mCXCR1 with high sensitivity (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Many gastrointestinal disorders (GD), such as dyspepsia, gastroesophageal reflux disease (GERD), and inflammatory bowel disease (IBD), are closely linked to chronic inflammation and cellular damage in the gastrointestinal tract due to excessive oxidative stress [ 25 , 26 ]. Recent clinical research has indicated that H. pylori , containing the CagA virulence factor, can induce increased levels of reactive oxygen species (ROS) in plasma [ 27 ]. Therefore, boosting antioxidative capacity has emerged as a promising therapeutic approach for managing various gastrointestinal diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%